Amorphous IGZO field effect transistor based flexible chemical and biosensors for label free detection - Bhatt, Deepa; Kumar, Satyendra; Panda, Siddhartha (Flexible and printed electronics, 2020)
Flexible chemical sensors and biosensors are of interest in different industry sectors and have advantages for being shape-friendly, lightweight, with potential of low cost. The performance factors such as fast response and label free detection makes field effect transistors an attractive platform for such sensors. While there is a large body of literature on ion sensitive field effect transistors using rigid substrates, limited studies are reported on flexible substrates. Electrolytic gated field effect transistors, a class of ion sensitive field effect transistors, have a further advantage as no gate dielectrics are needed (with the electrolytic solution itself acting as the gate dielectric) and need lower operating voltages; there are no reports yet of electrolytic gated field effect transistor with amorphous indium gallium zinc oxide as the semiconductor as well as a sensing layer on flexible substrates and this is the subject of the present work, where fully flexible electrolytic gated field effect transistors are demonstrated on flexible polyethylene terephthalate substrates for pH sensing and for detection of prostate specific antigen. Bottom contact electrolytic gated field effect transistors structures with indium tin oxide as the source and drain were fabricated on flexible polyethylene terephthalate substrates with amorphous indium gallium zinc oxide as the semiconductor deposited over indium tin oxide at room temperature. Materials and electrical characterizations (in a low operating voltage range of −1-1.5 V) were conducted. A pH sensitivity of 20 2 mV pH−1 was demonstrated. Stability studies and bending tests were also conducted. Label-free bio-sensing for prostate specific antigen was demonstrated in the concentration range 1 pg ml−1-10 ng ml−1 in phosphate buffer saline. This learning can be utilized to fabricate wearable sensors for healthcare monitoring at low cost.